Moderating effects of SRI-KEHATI on the ESG-corporate value nexus - Andanawarih, Parasdya Pandhu; Hasanah, Anisaul; Mila, Shofiatul (Diponegoro International Journal of Business, 2024)
Environmental, social, and governance (ESG) activities have become crucial and practical for corporations due to growing concerns over these issues. This research aims to measure the impact of ESG and Dividend Yield (DY) on corporate value (CV), using Tobin's Q ratio as a proxy for CV. We analyzed a sample of 25 companies listed in the SRI KEHATI Index from 2010 to 2019, using panel data methods to assess the relationships between ESG, DY, and CV. Additionally, we examined the SRI KEHATI Index's moderating role in this context. The study found a significant negative relationship between ESG and CV, while DY positively and significantly influenced CV. When the SRI KEHATI Index is used as a moderator, it significantly enhances the positive impact on ESG and CV. This research enhances understanding of the ESG-DY-CV relationship, aiding corporations in strategy formulation and helping stakeholders with investment decisions. Its originality lies in studying the SRI KEHATI Index's moderating effects, providing a foundation for future research.